Assessment of Inorganic Chemical Composition of PM2.5 Aerosols in Tiaret-City, Algeria - Naceur Khadidja; Maatoug Mohamed; Belarbi El Habib; Serge Bresson; Stefan Henfling (Challenges and Advances in Chemical Science Vol. 7, 2021)
The objective of this work is to determine and quantify the inorganic compounds of PM2.5 aerosols; collected using a two-stage Dekati® PM10 impactor; in educational establishments in Tiaret-city "Algeria". It also aimed to follow the dispersion of these particles in sites near the forest, urban fabric and urban sites exposed to dense road traffic, as well as to determine the source of this type of pollution. 23 primary schools were chosen as sampling sites in Tiaret city. The collection of PM2.5 was carried out in the winter and summer period. The spectroscopic analysis carried out by FTiR-ATR shows that the sulfate ions recorded their maximum in the summer period than in the winter, as well as the nitrate and ammonium ions which do not show a large seasonal difference. The dominant species in urban areas are NO3-, SO4-2 which due to the presence of a very important source of NOx and SO2 which, by gas-particle conversion, transform into nitrate and sulfate ions respectively. These species present a lower proportion in sites close to the forest. However, the same order of abundance of these ions exists in the two sampling periods. The main sources of NOx in urban sites are combustion phenomena linked in particular to the transport system, which is characterized by very dense traffic in the city’s agglomeration.